POLA KOMUNIKASI ORANG TUA DENGAN ANAK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA MASA PANDEMI COVID-19 DI SEKOLAH MENENGAH ATAS (SMA) NEGERI 1 CILAMAYA KABUPATEN KARAWANG - Pawit Bustami (MUMTAZ : Jurnal Pendidikan Agama Islam, 2021)
This study aims to analyze the communication patterns of parents and children in communicating Islamic Religious Education learning during the Covid-19 pandemic at State 1 Cilamaya Karawang High School. This study uses a qualitative approach. Data mining based on interviews and document review. This study involved several informants including five parents of students, four teachers of Islamic religious education and five students. The results of this study indicate that communication patterns in Islamic Religious Education learning between parents and students are direct communication patterns, indirect communication patterns, communication processes carried out in an approach, and communication patterns carried out democratically.